Le topos « Bonus dormitat Homerus » et ses récurrences françaises au XVIIe siècle - Pawłowska, Maja (Romanica Silesiana, 2021)
The present paper outlines the main characteristic of the topos “the good Homer sometimes nods”, introduced in Horace’s Epistle to the Pisones, and its French late 16th and 17th-century recurrences.